Expert-Like Use of Hedges and Boosters in Research Articles Written by Polish and English Native-Speaker Writers - Hryniuk, Katarzyna (Research in Language, 2018)
The present study compares the use of main interpersonal metadiscourse markers - hedges and boosters - in a corpus of 40 research articles from the area of applied linguistics, written in English by native speakers and Polish writers. Used as communicative strategies, these words and expressions increase (boosters) or reduce (hedges) the force of arguments. In order to gain an in-depth insight and to achieve greater precision, in the analysis the author utilizes a concordance tool WordSmith 6.0 (Scott 2012). The results point to important discrepancies in the usage of these text features by authors representing different native languages and cultures. The study has important implications for developing competence in writing for publication in English as a Foreign Language.